Desiccation crisis of saline lakes: A new decision-support framework for building resilience to climate change - Hassani, Amirhossein; Azapagic, Adisa; D'Odorico, Paolo; Keshmiri, Amir; Shokri, Nima (The Science of the total environment, 2020)
[Display omitted] •An eco-hydrological framework is developed to restore desiccating saline lakes.•A wide range of climatic, hydrologic, and agronomic stressors are considered.•Parts of the lake that should be prioritized for restoration can also be identified.•Alternative cropping patterns and land-use change are determined for restoration.•The framework applicability is demonstrated through the case of Lake Urmia in Iran. River flow reductions as a result of agricultural withdrawals and climate change are rapidly desiccating endorheic lakes, increasing their salinity and affecting the bio-diversity and human wellbeing in the surrounding areas. Here we present a new framework to guide eco-hydrological restoration of saline lakes and build their resilience to climate change by optimizing agricultural land use and related water withdrawals. The framework involves four steps: 1. selection of global circulation models for the basin under study; 2. establishment of a hydrological balance over the lake’s area to estimate the amount of water required for its restoration; 3. water allocation modeling to determine the water available for restoration and allocation of the remaining water across different users in the lake’s basin; and 4. basin-scale optimization of land use and cropping patterns subject to water availability. We illustrated the general applicability of the framework through the case of the second largest (by volume) hyper-saline lake globally, Lake Urmia, which lost 96% of its volume in only 20 years, primarily as a result of upstream water withdrawals. Through the application of the framework, we estimated the amount of water needed to restore the lake, either fully or partially, and proposed a sustainable land-use strategy, while protect farmers’ income in the basin. Considering future climate change projections under two representative concentration pathways (RCP) 4.5 and 8.5, we found that an average annual surface inflow of 3,648 Mm3 (∼70% increase in RCP 4.5) and 3,692 Mm3 (∼73% increase in RCP 8.5) would be required to restore the lake by 2050, respectively. This would require the respective conversion of 95,600 ha and 133,687 ha of irrigated land to rain-fed cropland or grassland across the basin by 2050. The proposed framework can be used for building resilience to climate change and mitigating human-induced threats to other declining saline lakes.